Förutsättningar för återintroduktion av stora gräsätare i Sverige - Lindblad, Erland (SLU/Dept. of Animal Environment and Health (until 231231), 2011)
Biodiversity is under threat in Sweden and many species are on the brink of extinction. This is mainly due to the large-scale drainage projects during the 19th and 20th century and the increasingly intensive land use in agriculture and forestry. The intensive land use with sharply defined boundaries between the production units has in many cases led to either overgrazing or overgrowing. As a result many species have been pushed back to "leftover" habitats like shooting ranges, power line corridors, roadsides, dumps, embankments and other similar areas. Therefore the question has been raised, wether or not it is needed to re-introduce large herbivores into the wild in order to maintain the biodiversity that is related to the extensive land use.